Atividade antinociceptiva orofacial do (S)-(-)-álcool perílico em camundongos: um estudo controlado, randomizado e triplo-cego - Morais, James Felipe Tomaz de (2015)
Monoterpenes are the major bioactive compounds found in essential oils from medicinal plants used in the treatment of diseases. Among these, (S)-(-)-perillyl alcohol (PA) stands as a promising molecule with antitumor, anti-inflammatory and antioxidant properties. This study investigated the antinociceptive effects of PA on orofacial nociception in Swiss male mice using tests of formalin-, capsaicin-, and glutamate-induced pain. For each test, eight animals per group were pretreated intraperitoneally by a blinded investigator with PA (50 and 75 mg/kg, i.p.), morphine (5 mg/kg, i.p.) or vehicle (saline + 0.2% Tween 80). The treatment was performed thirty minutes before the induction of orofacial nociception by injecting formalin (20 µl, 2%), capsaicin (20 µl, 2.5 µg) or glutamate (40 µl, 25 mM) solution in the right area of the upper lip. The orofacial nociceptive behavior was timed in all tests by an investigator blinded to the treatments. Statistical analysis was performed by a blinded researcher. Groups were compared with Mann-Whitney’s test and the correlation was calculated with Spearman’s correlation test, describing its median and interquartile range. The magnitude of statistical analysis was also analyzed with confidence intervals, effect size and power. The results indicate that PA blocked the orofacial nociceptive behavior at all tested doses (P <.05) similarly to morphine (P > .05) in the formalin, capsaicin and glutamate tests. Effect size was high in phase I of formalin test for 50 mg/kg and 75 mg/kg of PA (CI95%: 2,32/0,48; power: 84% and CI95%: 2,76/0,82; power: 96.2%, respectively), 75 mg/kg of PA in phase II (CI95%: 2,26/0,44; power: 82.3%) and for 75 mg/kg of PA in glutamate test (CI95=3,16/1,11; power: 99.2%). These findings confirm a strong evidence of antinociceptive properties of PA in the orofacial region considering high values of power observed in formalin and glutamate models, suggesting it as a potential substance for the treatment of clinical conditions involving orofacial pain.